Waqf Development in Indonesia: R Application - Puspita, Amelia Tri; Tanjung, Hendri (SMART Insight, 2023)
The paradigm shift in waqf development also occurred in Indonesia. This change was initiated by waqf reform from the legal-constitutional and institutional aspects, with the aim of improving the performance of waqf in the country. Legally-constitutionally, waqf reform is covered by Law (UU) No. 41/2004 on Waqf and Government Regulation (PP) No. 42/2006 as an implementation guideline for Law No. 41/2004. This study aims to determine the development of waqf development in Indonesia research trends published by leading journals on Islamic economics and finance. The data analyzed consisted of 58 indexed research publications. The data is then processed and analyzed using the R application to determine the bibliometric map of waqf development research development in Indonesia. Some analyzes such as word clouds, trend topics, thematic map and also thematic evolution on waqf development in Indonesia are also displayed.